Inverted variant of urothelial carcinoma of the urinary bladder: a report of three cases and a proposal for a new clinicopathologic entity - Terada, Tadashi (e-Century Publishing Corporation, 2013)
Inverted urothelial carcinoma (UC) without papillary areas is very rare; only 31 cases of three papers have been reported. The author herein reports three additional cases, and proposes the term “inverted variant” (IV) of UC. The materials were 3 cases of IV of UC, 5 cases of inverted papilloma (IP), and two cases of nested variant (NV) of UC. The three cases of IV of UC consisted of 56-year-old woman, 63-year-old man, and 78-year-old man. Presenting symptoms were hematuria in all cases. The cystoscopic findings were elevated tumors without papillary proliferations in all cases. The treatment was transurethral tumor resection (TUR-BT) in all cases. The sizes was 0.6 cm, 0.5 cm, and 3 cm. Microscopically, IV of UC showed inverted growth of atypical cells without papillary proliferations. Compared to IP, the inverted growth pattern was similar, but cytological atypia and thick trabeculae were noted in IV of UP while they were absent in IP. Compared to NV of UC, the growth pattern is different; NV of UC showed nested and vague tubular pattern. The cellular atypia is more pronounced in IV of UC than NV of UC. Immunohistochemically, p53 expression was seen in all the cases of IV of UC and in all the cases of NV of UC, while p53 expression was negative in all the cases of IP. Ki-67 labeling index was 25, 30 and 40% in IV of UC, 15 and 30% in NV of UC, and 3, 5, 6, 7, 9% in IP. Invasive features were seen in 1 case of IV of UC and 2 cases of NV of UC. In all cases of IV of UC, IP, and NV of UC, the TUR-BT, but one case of IV of UC, showed no recurrence after TUR-BT, while one case of IV of UC showed a recurrence. In conclusion, the IV and UC were structurally and cytologically very different from the NV of UC. The IV of UC was structurally similar to IP, but cellular atypia and thickened trabeculae were seen in IV and UC. p53 expression and Ki-67 labeling status were entirely different between in IV of UC and IP. The author proposes the term of IV of UC as a new clinicopathological entity.